2016
DOI: 10.7860/jcdr/2016/16187.7015
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Intradural Schwannoma with Acute Intratumoural Haemorrhage: Case Report and Review

Abstract: Schwannomas account for around half of all intradural spinal tumours, with chronic progressive symptoms as the most common presenting features. Intratumoural haemorrhage as a presenting feature of spinal schwannoma is very rare and only 11 cases have been reported till date. Authors here report a previously asymptomatic 40-year-old male who presented with acute onset paraplegia 12 hours after a minor trauma. MR imaging revealed a C7-D3 intradural-extramedullary lesion with features of acute blood and showing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Hemorrhagic type of spinal schwannoma is a rare case and more commonly found in the cranial region of the spine [5]. The tumor in the spine is more likely found around the thoracolumbar junction region or the cervical region due to the high movement in these segments and the high density of the nerve roots [25]. The difference between this type of schwannoma and other types is the clinical finding of bleeding in the tumor mass intraoperatively.…”
Section: Hemorrhagic Type Of Spinal Schwannomamentioning
confidence: 99%
See 3 more Smart Citations
“…Hemorrhagic type of spinal schwannoma is a rare case and more commonly found in the cranial region of the spine [5]. The tumor in the spine is more likely found around the thoracolumbar junction region or the cervical region due to the high movement in these segments and the high density of the nerve roots [25]. The difference between this type of schwannoma and other types is the clinical finding of bleeding in the tumor mass intraoperatively.…”
Section: Hemorrhagic Type Of Spinal Schwannomamentioning
confidence: 99%
“…The difference between this type of schwannoma and other types is the clinical finding of bleeding in the tumor mass intraoperatively. From microscopic findings, it is shown that the hemorrhagic background along with Verocay bodies, spindle-shaped Schwann cell areas (Antoni type A tissue), and loose myxoid area (Antoni type B tissue) [58].…”
Section: Hemorrhagic Type Of Spinal Schwannomamentioning
confidence: 99%
See 2 more Smart Citations
“…Schwannomas comprise nearly 50% of all intradural spinal tumors, with chronic progressive symptoms as the most common clinical presentation [1]. They are benign tumors arising from nerve roots and based on their location they can take the form of a dumbbell-shaped mass [2].…”
Section: Introductionmentioning
confidence: 99%